PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAMPERJANJIAN JUAL BELI ONLINE - Maulfie Nur Aufa Sagra (2021)
Information technology in the future as a primary alternative is believed to be able to increase the efficiency and speed of business management, such as trading and buying and selling activities through electronic media (E-commerce). E-commerce transactions have many advantages, but Ecommerce transactions can also cause problems that are carried out by various parties such as the marketplace. Thus, this study has the aim of knowing and understanding the legal protection of the marketplace for consumers, as well as the responsibility of the marketplace to consumers in online buying and selling agreements. This research is normative legal research with a statutory approach method and secondary data sources, as well as qualitative descriptive data analysis techniques. Then the results obtained from this legal research (1) The state has a role to protect E-commerce consumers with regulations and policies both preventive and repressive. (2) There are two forms of marketplace legal relations in Indonesia, including the Consumer to Consumer (C2C) marketplace and the Business to Consumer (B2C) marketplace, then the marketplace is responsible for losses incurred by consumers following the marketplace legal relationship itself.